Harnessing phage biocontrol strategies for managing bacterial plant pathogens - Sajad Ali; Tarequl Islam; Mohammed A Almalki; Muhammad Fazle Rabbee (BioControl, 2026)

Development of dry and oil-based formulations of Metarhizium anisopliae using carrier materials for effective control of red flour beetle, Tribolium castaneum (Coleoptera: Tenebrionidae) - Nahdia Perveen; Abu Bakar Muhammad Raza; Muhammad Arshad; Panagiotis Eliopoulos; Samah F. Ibrahim; Mustafa Shukry; Samy Sayed; Hanan M. A. Hamada (BioControl, 2026)

First records of diurnal and nocturnal predatory birds from artificial hunting perch trials in oil palm plantations - Kamil Tohiran; Dzulhelmi Muhammad Nasir; Maisarah Burhanuddin; Frisco Nobilly; Raja Zulkifli; Ramle Moslim; Muhammad Syafiq Yahya; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (BioControl, 2024)

Do silvopastoral management practices affect biological pest control in oil palm plantations? - Frisco Nobilly; Sharifah Nur Atikah; Muhammad Syafiq Yahya; Shokri Jusoh; Thomas M. R. Maxwell; Ahmad Razi Norhisham; Kamil Azmi Tohiran; Raja Zulkifli; Badrul Azhar (BioControl, 2023)

Rice-associated antagonistic bacteria suppress the Fusarium fujikoroi causing rice bakanae disease - Mah-E-Neema Nawaz; Kamran Malik; Muhammad Nadeem Hassan (BioControl, 2022)

Biological control of strawberry crown rot, root rot and grey mould by the beneficial fungus Aureobasidium pullulans - Mudassir Iqbal; Maha Jamshaid; Muhammad Awais Zahid; Erik Andreasson; Ramesh R. Vetukuri; Johan A. Stenberg (BioControl, 2021)
Utilization of biocontrol agents is a sustainable approach to reduce plant diseases caused by fungal pathogens. In the present study, we tested the effect of the candidate biocontrol fungus Aureobasidium pullulans (De Bary) G. Armaud on strawberry under in vitro and in vivo conditions to control crown rot, root rot and grey mould caused by Phytophthora cactorum (Lebert and Cohn) and Botrytis cinerea Pers, respectively. A dual plate confrontation assay showed that mycelial growth of P. cactorum and B. cinerea was reduced by 33–48% when challenged by A. pullulans as compared with control treatments. Likewise, detached leaf and fruit assays showed that A. pullulans significantly reduced necrotic lesion size on leaves and disease severity on fruits caused by P. cactorum and B. cinerea . In addition, greenhouse experiments with whole plants revealed enhanced biocontrol efficacy against root rot and grey mould when treated with A. pullulans either in combination with the pathogen or pre-treated with A. pullulans followed by inoculation of the pathogens. Our results demonstrate that A. pullulans is an effective biocontrol agent to control strawberry diseases caused by fungal pathogens and can be an effective alternative to chemical-based fungicides.

Demographic parameters of the reduviid predator, Rhynocoris marginatus (Reduviidae: Hemiptera) fed on two lepidopterous insect pests - Muhammad Arshad; Muhammad Irfan Ullah; Rashad Rasool Khan; Sana Anjum; Muhammad Tahir; Adeela Shamshad; Muhammad Rizwan (BioControl, 2021)

Evaluation of host–pathogen interactions for selection of entomopathogenic fungal isolates against Oligonychus afrasiaticus (McGregor) - Abid Hussain; Muhammad Rizwan-ul-Haq; Ahmed Mohammed AlJabr; Hassan Al-Ayedh (BioControl, 2020)

Bioherbicidal activity of allelopathic bacteria against weeds associated with wheat and their effects on growth of wheat under axenic conditions - Tasawar Abbas; Zahir Ahmad Zahir; Muhammad Naveed (BioControl, 2017)

Plant growth promoting rhizobacteria suppress blast disease caused by Pyricularia oryzae and increase grain yield of rice - Afroz Rais; Muhammad Shakeel; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (BioControl, 2016)

Effect of Beauveria bassiana infection on the feeding performance and antioxidant defence of red palm weevil, Rhynchophorus ferrugineus - Abid Hussain; Muhammad Rizwan-ul-Haq; Hassan Al-Ayedh; Sohail Ahmed; Ahmed Mohammed Al-Jabr (BioControl, 2015)

Suppression of red rot disease by Bacillus sp. based biopesticide formulated in non-sterilized sugarcane filter cake - Muhammad Nadeem Hassan; Namood-e-Sahar; Syed Zia-Ul-Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2015)

Molecular identification of Trichogramma species from Pakistan, using ITS-2 region of rDNA - Muhammad Farooq Nasir; Gregor Hagedorn; Carmen Büttner; Christoph Reichmuth; Matthias Schöller (BioControl, 2013)

Erratum to: Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)

Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)